Umrah mobile application in augmented reality (UMAAR) / Nur Atiqah Ismail - Ismail, Nur Atiqah (2017)
Mobile Application tends to increase around the worldwide. It is spreading in all aspects in life including the religion. Umrah Mobile Application in Augmented Reality is one of the applications in religion. Currently, there is many Umrah Mobile Application existed in the market but it is not satisfied the requirements of the user. Apart from that, this study suggested the new way in delivery the knowledge regarding the Umrah which is Augmented Reality (AR). This study tends to identify the current problems in the existing Umrah Mobile Application and identify the requirements need from the user in Umrah Mobile Application by the previous research and also the interviews. The interview discovers about their experience in getting the knowledge of Umrah. The following results are expected to be achieved: a) The requirements to Umrah Mobile Appication; b) A prototype of Umrah Mobile Application in Augmented Reality (UMAAR) The result of this study will become a reference to the developers in developing the Umrah Mobile Application in Augmented Reality(UMAAR) for the pilgrims.